Access control system using beacon-based indoor location data pattern analysis - Gwang Lee, Jae; Pil Lee, Jae; Su Mo, Eun; Hyeon Lee, Jun; su Yoon, Ki; Kwang Lee, Jae (International Journal of Engineering and Technology, 2018)
Background/Objectives: With the development of IT, accidents of industrial secret leakage have occurred more than before. Such acci-dents are mostly caused by insiders. Methods/Statistical analysis: An existing access control system uses RFID and NFC tag. The system saves only the final location in-formation in DB. For the reason, it is hard to track a user’s location data in real time. However, a beacon-based access control system saves a user’s location information in DB in real time. By analyzing the location information of DB, it is possible to track a user. Findings: Beacons are used for determining a user’s location. The determined location information is converted into location data which is saved into DB. The location data is converted into coordinates. The converted coordinate data is analyzed for understanding a user’s behavior pattern. In the pattern analysis, if a user takes an abnormal behavior, policy-based response is performed. The user behavior pattern analysis system proposed in this study is able to respond to an accident in real time. Therefore, it is expected to contribute to reducing the number of industrial secret leakage accidents caused by insiders. Improvements/Applications: This study designs a model that analyzes behavior pattern by using the indoor location data of a user based on beacon.